Ventricular volumes across stages of schizophrenia and other psychoses. (October 2017) - Berger, Gregor E; Bartholomeusz, Cali F; Wood, Stephen J; Ang, Anthony; Phillips, Lisa J; Proffitt, Tina; Brewer, Warrick J; Smith, Deidre J; Nelson, Barnaby; Lin, Ashleigh; Borgwardt, Stefan; Velakoulis, Dennis; et al.
Objective: Ventricular enlargement is common in established schizophrenia; however, data from ultra high-risk for psychosis and first-episode psychosis studies are inconclusive. This study aims to investigate ventricular volumes at different stages of psychosis. Methods: Ventricular volumes were measured using a semi-automated and highly reliable method, for 89 established schizophrenia, 162 first-episode psychosis, 135 ultra high-risk for psychosis and 87 healthy controls using 1.5T magnetic resonance images. Clinical outcome diagnoses for ultra high-risk for psychosis were evaluated at long-term follow-up (mean: 7.5 years). Results: Compared to controls, we identified significant ventricular enlargement of 36.2% in established schizophrenia ( p < 0.001). Ventricular enlargement was not significant in first-episode psychosis (6%) or ultra high-risk for psychosis (−3%). Examination across stages of schizophrenia-spectrum diagnoses subgroups revealed a significant linear trend ( p = 0.006; established schizophrenia = 36.2%, first-episode psychosis schizophrenia = 18.5%, first-episode psychosis schizophreniform = −4.2% and ultra high-risk for psychosis-schizophrenia converters = −18.5%). Conclusion: Ventricular enlargement is apparent in patients with established schizophrenia but is not a feature at the earliest stages of illness (ultra high-risk for psychosis and first-episode psychosis). Further research is needed to fully characterize the nature and timing of ventricular volume changes early in the course of illness and how these changes impact outcomes.